2020
DOI: 10.1002/sd.2072
|View full text |Cite
|
Sign up to set email alerts
|

Bioeconomy futures: Expectation patterns of scientists and practitioners on the sustainability of bio‐based transformation

Abstract: Economic sectors relying on the use of biological organisms, processes, and principles to create products and services are expected to experience accelerated growth due to innovation in the bioeconomy. Associated benefits and risks for sustainable development are increasingly subject to societal debate. We compiled expectation patterns from a global survey with bioeconomy experts and a systematic literature review identifying areas of consensus and controversy across dimensions of the sustainable development g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 86 publications
(71 reference statements)
0
27
0
4
Order By: Relevance
“…Unlike inert materials, that need to be kept in closed-loops, biotic materials in a biobased economy are to be used in cascades, providing economic systems with greater degree of flexibility and adaptive capacity. However, the uncertainties surrounding massive transformations of product segments from fossil-based to biobased alternatives require careful valuation of sustainability risks (Biber-Freudenberger et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike inert materials, that need to be kept in closed-loops, biotic materials in a biobased economy are to be used in cascades, providing economic systems with greater degree of flexibility and adaptive capacity. However, the uncertainties surrounding massive transformations of product segments from fossil-based to biobased alternatives require careful valuation of sustainability risks (Biber-Freudenberger et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In redesigning the bioenergy sector, local knowledge, public health, and the community's resilience should not be neglected, while social-environmental benefits should be considered in addressing the viability of bioenergy plants [1]. For the time being, integration of bioenergy in a broader bioeconomy is an ambition rather than a substantiated way [7][8][9]. This study has already demonstrated the diversity of options and implications of bioenergy.…”
Section: (I) From Mono-substrates To Diverse Substrates With Alternamentioning
confidence: 91%
“…Energy represents one SDG (Affordable and Clean Energy) with priorities on renewables. Bioenergy can make a significant contribution in that respect [8]. Biomass production and its use for energy supply interfere with several other SDGs, i.e., Life on Land, Zero Hunger, or Responsible Production and Consumption.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies indicated that process innovations are fundamental for reducing carbon emissions by changing from carbon-emitting fossil fuels to renewable energy, promoting energy conservation and efficiency [20,21] and bioeconomy, such as organic food cultivation, plays a special rule in green growth [13]. Biber-Freudenberger, L. et al [22] is associated bioeconomic sectors with innovations. In the case of the food and feed sector, the main innovations are organic farming, integrated pest management and ecological intensification.…”
Section: Introductionmentioning
confidence: 99%